18O proteomics reveal increased human apolipoprotein CIII in Hispanic HIV‐1+ women with HAART that use cocaine. Issue 2 (19th November 2015) - Zenón, Frances; Jorge, Inmaculada; Cruz, Ailed; Suárez, Erick; Segarra, Annabell C.; Vázquez, Jesús; Meléndez, Loyda M.; Serrano, Horacio
Abstract : Purpose: Drug abuse is a major risk factor in the development and progression of HIV‐1. This study defines the alterations in the plasma proteome of HIV‐1‐infected women that use cocaine. Experimental design: Plasma samples from 12 HIV‐seropositive Hispanic women under antiretroviral therapy were selected for this study. Six sample pairs were matched between nondrug users and cocaine users. After IgG and albumin depletion, SDS‐PAGE, and in‐gel digestion, peptides from nondrug users and cocaine users were labeled with 16 O and 18 O, respectively, and subjected to LC‐MS/MS and quantitation using Proteome Discover and QuiXoT softwares and validated by ELISA. Results: A total of 1015 proteins were identified at 1% false discovery rates (FDR). Statistical analyses revealed 13 proteins with significant changes between the two groups, cocaine and noncocaine users ( p < 0.05). The great majority pertained to protection defense function and the rest pertained to transport, homeostatic, regulation, and binding of ligands. Apolipoprotein CIII was increased in plasma of HIV+ Hispanic women positive for cocaine compared to HIV+ nondrug users ( p ≤ 0.05). Conclusions and clinical relevance: Increased human apolipoprotein CIII warrants that these patients be carefully monitored to avoid the increased risk of cardiovascular events associated with HIV, HAART, and cocaine use.